2006
DOI: 10.1111/j.1365-2303.2006.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cytology of clear cell carcinoma of the ovary

Abstract: Using cytological analysis of imprint and scraping samples of ovarian tumours it is possible to make a precise intraoperative cytological diagnosis in most cases of CCC of the ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 11 publications
(26 reference statements)
3
29
2
Order By: Relevance
“…It is recognized that the accurate intraoperative diagnosis of ovarian clear cell carcinomas can be particularly problematic because these tumors exhibit a wide variety of histological patterns that can mimic other primary and secondary ovarian tumors. 28 It has been suggested that cytological preparations may be particularly helpful in the diagnosis of these tumors, notably in highlighting their characteristic hyaline stroma, 29,30 but this feature was not seen in all of the cases in this study. Not surprisingly, rare ovarian tumors also caused greater difficulty in the intraoperative setting and these sometimes elicited a nonspecific or differential diagnosis.…”
Section: Discussionmentioning
confidence: 44%
“…It is recognized that the accurate intraoperative diagnosis of ovarian clear cell carcinomas can be particularly problematic because these tumors exhibit a wide variety of histological patterns that can mimic other primary and secondary ovarian tumors. 28 It has been suggested that cytological preparations may be particularly helpful in the diagnosis of these tumors, notably in highlighting their characteristic hyaline stroma, 29,30 but this feature was not seen in all of the cases in this study. Not surprisingly, rare ovarian tumors also caused greater difficulty in the intraoperative setting and these sometimes elicited a nonspecific or differential diagnosis.…”
Section: Discussionmentioning
confidence: 44%
“…Finally, the extracellular hyaline material evident on the smear preparations would be an unusual finding in most ovarian epithelial neoplasms with the possible exception of clear cell carcinoma. 23,24 In our experience, the intraoperative diagnosis of ovarian clear cell carcinoma can present particular difficulty, 25 but the neoplastic cells generally are large, and cytologic material from clear cell carcinomas usually demonstrates 3-dimensional Braspberry[ bodies, a glycogen-rich background, and high-grade nuclei, features that were not identified in the current case. Anecdotally, however, we have also encountered metachromatic hyalinelike material in intraoperative cytologic preparations from other rare epithelial tumors including cases of corded and hyaline endometrioid adenocarcinoma and adenoid cysticlike carcinoma of the ovary.…”
Section: Discussioncontrasting
confidence: 50%
“…Interestingly, recent cytological studies have also emphasized the diagnostic value of hyaline stromal change in CCC because this has distinctive metachromatic appearances in air-dried preparations. Therefore, cytology smears or imprints may be a useful adjunct to frozensection diagnosis in the intraoperative assessment of CCC and other ovarian tumors (36,37).…”
Section: Clear Cell Carcinoma Of the Ovarymentioning
confidence: 99%